The Effect of Leverage, Liquidity, and Activity on Stock Price with Profitability as a Moderating Variable - Rahmi, Raisa; Kholilah, Kholilah (Universitas Muhammadiyah Metro, 2024)
The research objective is to know the Effect of Leverage, Liquidity, and Activity Ratios on Stock Prices with Profitability as a Moderating Variable in Property and Real Estate Companies Listed on the IDX for 2018-2022. This research is quantitative research. 54 firms listed between 2018-2020 on the Indonesia Stock Exchange contribute to the research population. Purposive sampling was used for the sampling process, yielding 80 firms based on predetermined standards—data analysis using SPSS with multiple and moderated regression analysis. The findings demonstrated that activity ratio positively impacted stock prices, leverage and liquidity had a negative and significant impact. Moreover, the research results indicate that the effect of leverage, liquidity, and activity on stock price cannot be mitigated by profitability, the moderating variable. It is advisable to enhance the sample size of companies under investigation and extend the duration of the research to ensure greater accuracy in the obtained results. Future studies should also consider adding independent variables to increase the complexity of the analysis